LACK OF JOB OPPORTUNITY: a reality of the LGBTQIAP+ population - de Oliveira Machado, Thalia; Garcia Ferreira, Paulo Alberto; Segnini Rodrigues, Lilian (Revista Interface Tecnológica, 2023)
The main objective of this article is to analyze the barriers faced by the LGBTQIAP+ community in the recruitment and selection process in São Carlos (SP). For this, we used an online questionnaire, with specific questions to understand the difficulties experienced by LGBTQIAP+ people in selection processes. The results obtained were unexpected, due the majority of respondents did not report that their sexual orientation or gender identity was a feature of their ability to be selected in selection processes, it raises the question of whether not sharing this information might have had a positive impact on the results. Thus, this study underscores the complexity of these issues and underscores the need for further in-depth investigations to understand how gender identity and sexual orientation interact in the context of recruitment and selection.